4E-BP1, a multifactor regulated multifunctional protein. Issue 6 (18th March 2016) - Qin, Xiaoyu; Jiang, Bin; Zhang, Yanjie
ABSTRACT: Eukaryotic translation initiation factor 4E (eIF4E)-binding protein 1 (4E-BP1) is a member of a family of translation repressor proteins, and a well-known substrate of mechanistic target of rapamycin (mTOR) signaling pathway. Phosphorylation of 4E-BP1 causes its release from eIF4E to allow cap-dependent translation to proceed. Recently, 4E-BP1 was shown to be phosphorylated by other kinases besides mTOR, and overexpression of 4E-BP1 was found in different human carcinomas. In this review, we summarize the novel findings on mTOR independent 4E-BP1 phosphorylation in carcinomas. The implications of overexpression and possible multi-function of 4E-BP1 are also discussed.